Small Is Beautiful? Emerging Organizational Strategies among Italian Professionals. (5th July 2018) - Maestripieri, Lara; Cucca, Roberta
Abstract: The traditional debate about professional groups has mainly focused on conflicts between professions and organizations, reinforcing dualisms and dichotomies. Few scholars have investigated the extent to which professionalism and organizations are intertwined while focusing on the case of professionals integrated into large organizations, and even less attention has been paid to emerging forms of organization among self‐employed professionals. Taking as an example organizational trends among architects (liberal professionals) and management consultants (emerging professionals) in Italy, this article investigates how small, flexible, and (often) interprofessional organizations promoted by self‐employed professionals are increasingly instrumental in overcoming market pressures and responding to emerging social needs in times of crisis and austerity. Résumé: Le débat traditionnel à propos des groupes professionnels a principalement concerné les conflits entre professions et organisations, renforçant ainsi les dualisations et dichotomies entre ces deux groupes. Peu de chercheurs ont enquêté à quel point la profession et l'organisationnel sont interdépendants lors de l'étude de l'intégration de professionnels à de grandes organisations. En fait, moins d'attention a été portée aux formes organisationnelles émergentes entre les professionnels indépendants. En prenant exemple sur les architectes (professionnels libéraux) et les professionnels dans le conseil en management (professionnels émergents) qui travaillent en Italie, cet article analyse comment les organisations des professionnels indépendants, qui sont petites, flexibles et (souvent) interprofessionnelles, se transforment en outils pour faire face à la pression du marché et pour répondre aux besoins émergents en temps de crises et austérité.